Consistency of publication types and costs among Croatian Social Sciences journals - Stojanovski, Jadranka (Septentrio Conference Series, 2018)
This study provides an analysis of Croatian scholarly open access journals and funding scheme. It presents an integrated approach to the general journal properties, types of publications and applied business model, looking at (1) criteria for funding, (2) structure and frequency of different publication types, and (3) the price per peer-reviewed paper. It is based on an analysis of 60 journals from the field of social sciences funded by the Croatian Ministry of Science and Education and included in the repository of Croatian open access journals HRČAK. For each journal information on the title, ISSN (print and online), field, discipline and branch, publisher, DOI, frequency, publication formats, and funding received in 2017 were collected. There are six peer-reviewed publication types (original scientific paper, short communication, preliminary communication, review article, professional paper, conference paper) and 14 additional, non-peer-reviewed publication types (meeting abstract, editorial, curriculum vitae, essay, bibliography, news, reminiscence, obituary, book review, letter to the editor, erratum, acknowledgement, index, other) available on HRČAK to be assigned to each paper. According to HRČAK categorization the attribute „type of publication“ was assigned to each of 8262 papers published during the years 2013-2017. The consistency of the type of publication was checked in different sources (PDF, journal website, Scopus, Web of Science Core Collection). The data was collected in July 2018. Each journal eligible for funding is required to satisfy a set of necessary conditions (peer-review, open access and availability on HRČAK, indexing in international bibliographic databases, the proportion of articles in which at least one author is from Croatia, editorial processes according to international standards, regularity in publishing). All eligible journals are evaluated every year by criteria grouped as general criteria, indexing and citations, peer-review and editorial work. Our findings revealed the consistency in most common publication types: original scientific paper and review article. Analysis of other types of publications, peer-reviewed, and non-peer-reviewed, revealed inconsistency across various sources. Publication type is an essential part of the research assessment criteria, and more consistency is needed at international level. Average price for peer-reviewed papers in 2017 was 445 EUR ranged from 1213 EUR to 162 EUR per paper.